The Difference of Teaching Arabic Language Curriculum 13 and The Merdeka Curriculum at MI Ma'arif Kliwonan - Karimah, Lutfiatul; Khasanah, Silvi Nur; Kurniya Khurotin, Laila; Muttaqin, Zaenal; Sesinawati, Hana Mulya; Ulfa , Maria; Sunarko, Asep (AJIRSS: Asian Journal of Innovative Research in Social Science, 2023)
The curriculum is a teaching guideline that is applied at all levels of education in Indonesia. The curriculum is updated regularly to ensure the relevance and actuality of the learning material. This research is to determine differences in Arabic language learning at MI Ma’arif Kliwonan. The objectives of this research are (1) to find out if the subject matter presented is relevant to the curriculum (2) to know the standard of presentation of material written in each subject (3) to find out the differences in teaching between curriculum 13 and the Merdeka curriculum. This research uses qualitative research. The method used in writing this article is the field method, namely collecting data obtained from interviews.